From Protein Structure to Function via Computational Tools and Approaches. Issue 3 (1st March 2013) - Kolodny, Rachel; Kosloff, Mickey
Abstract The three‐dimensional structures of proteins are often considered fundamental for understanding their function. Yet, because of the complexity of protein structure, extracting specific functional information from structures can be a considerable challenge. Here, we present selected approaches and tools that we have developed to study and connect protein sequence, structure, and function spaces. First, we consider a global perspective of structure space and view the protein data bank (PDB) as a database. We highlight challenges in searching protein structure space and in using the PDB as the starting point for computational structural studies. Then we describe a function‐oriented view and show examples of how multiple protein structures can be used to extract insights about the function and specificity of proteins at the family level.